The Emergence of the Problem of Changing the Environmental Law Umbrella from the Creation of the Job Creation Act - Gunawan, Christabella (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Indonesia is a country with abundant natural resources. But according to the data obtained, Indonesia is not included in the top 10 ranking countries that are rich in natural resources. Even in terms of astronomy, geology, and waters, Indonesia should be able to enter the top 5 countries with abundant natural resources. In addition, Indonesia is also included in the top 100 richest countries with a rank of 98 with a GDP/GDP (Bruno Domestic Income) - PPP (Purchase Power Parity) of 13,998 US dollars or equivalent to Rp. 195 million. According to data, the contribution of investment to the national economy reaches 30 percent of GDP. Which indirectly invests plays a major role in improving the economy and welfare of the Indonesian people. On the other hand, investment is one of the determining factors where the exploitation of the nation's natural resources, both renewable and non-renewable, is maintained or will it disappear without a trace. This is because investment, which is one of the pillars of the nation's economy, exploits natural resources on a large scale which damages the environment and ecosystem of the area. Laws on the environment and those that regulate natural resources are also allegedly affected by the emergence of the Job Creation Law in 2020, which will be discussed in this journal, and the solutions that are expected to regulate the Environmental Law and the Job Creation Act can synergize to build the Indonesian nation to be greater again.